Ārāʻ al-Fuqahāʻ fī Tashrīḥ al-Juthuth al-Bashariyyah bi Kulliyyat al-Ṭib (Al-Zahra : Journal for Islamic and Arabic Studies, 2007)
Development of medical science which is grew rapidly often clash with the values of religious rules. This paper describes one of the issues medicines that are considered controversial among scholars namely the use of human body parts in the sciences medical.